Vibrations and chemical states of iron ions in soda‐lime glasses determined by element‐specific X‐ray analyses. (21st June 2018) - Okada, Kyoko; Nagashima, Yukihito; Shiraki, Koichi; Kageyama, Hiroki; Ofuchi, Hironori; Yoda, Yoshitaka; Kobayashi, Yasuhiro; Umesaki, Norimasa; Sakurai, Yoshiharu
Abstract : We systematically study medium‐range structures including more than three neighboring atoms around iron ions (Fe 2+ and Fe 3+ ) in soda‐lime glass samples with low iron oxide concentrations (MFe2O3 ) and a wide number ratio of Fe 2+ to all iron ions (Fe 2+ /Σn Fe). The precise medium‐range structures around iron ions in glass have not yet been revealed because of a lack of the appropriate measurement methods. To avoid this problem, we used element‐specific nuclear resonant inelastic scattering (NRIS) with synchrotron X‐rays to observe the vibrations of iron ions ( 57 Fe). The vibrations are related to medium‐range structures with more than three neighboring atoms and to the potential asymmetry and the coordination environment, around iron ions. The NRIS method has high sensitivity and can measure over a wide concentration range. Linear combination fitting of the X‐ray absorption fine structure spectra, which measures only the first neighbors but is a faster than using the NRIS method, was also used additionally. A systematically produced set of glasses with 0.015–5 wt% MFe2O3 and 0–0.85 Fe 2+ /Σn Fe was measured with these methods. It was found that the soda‐lime glass possessed two different medium‐range structures with different iron ion valences (~2+ or ~3+), which were determined by the Fe 2+ /Σn Fe, and that these structures were generated during production of the glass. Moreover, these medium‐range structures were the same from 0.015 to 5 wt% MFe2O3 .